PLANNING TO SHIFT THE PERIMETER FENCE AT STA 1+300 TO STA 1+950 TO MEET THE SIDE STRIPE STANDARDS AT JUWATA TARAKAN INTERNATIONAL AIRPORT - Wibawa Pratama, Bagas; Wasito, Bambang; Meilawati Eka, Karina (Proceeding of International Conference of Advanced Transportation, Engineering, and Applied Social Science, 2023)
The planning of shifting the perimeter fence at Juwata Tarakan International Airport aims to meet side stripe standards and keep people and animals out, protect vital objects such as navigation or power plants, as a boundary marker for areas under airport control, and protect employees and employees. This will directly or indirectly affect flight safety at Juwata Tarakan International Airport. This condition can realize optimal security at the perimeter of Juwata Tarakan International Airport, it is necessary to implement flight rules that have been determined so as to support safe, smooth, comfortable and efficient flight operations that take place at Juwata Tarakan International Airport. In planning to shift the perimeter fence at Juwata Tarakan International Airport, not only changing the location but also calculating the budget plan and changing the existing foundation to a river stone foundation and displaying ground elevation data on the edge of the runway. In planning to shift the perimeter fence, it was found that the volume of landfill was 181 m3 and the volume of river stone foundations was 491 m3 and the results of the calculation of the budget plan were found to be Rp. 1,170,000,000.00 (one billion one hundred and seventy million rupiah). In addition to the budget plan for planning the shifting of the perimeter fence, the maintenance that will be carried out to prevent it from being corrosive is to apply anti-corrosive paint regularly